Gestion des ecosystemes forestiers denses d'Afrique tropicale humide: 2. Congo - Dupuy, B.; Loumeto, Jean Joël; Amsallem, I.; Gerard, C.; Nasi, Robert (Centre de Coopération Internationale en Recherche Agronomique pour le Développement, 1999)
This bibliography for the Republic of Congo is a sequel to the one on Gabon. It comprises 312 annotated references on thematic areas: fauna, flora, vegetation, ecology, conservation, silviculture, forest inventory, forest management, forest policy and economy, non-timber forest products, etc.; and a 20-page presentation of the country and its forests.